Nutrient Expert Impact on Yield and Economic In Maize and Wheat - Dahal, Sahara; Shrestha, Abhisek; Dahal, Sabina; Amgain, Lal Prasad (International Journal of Applied Sciences and Biotechnology, 2018)
The lower productivity and higher yield gaps in major cereals are the dominant problems of agriculture in eastern-terai of Nepal. Hence, field experiment was conducted to evaluate Nutrient Expert® wheat and maize model on farmer’s field at two sites each for maize and wheat in Morang and Jhapa district. The experiment was conducted in Randomized Completely Block Design replicated among twenty farmers in each district. Two treatments executed were NE (Nutrient Expert Recommendation) and FFP (Farmer Fertilizer Practices).The result revealed significant difference in terms of morphology, yield attributes and yield of wheat and maize. The highest wheat yield (4.71 ton ha-1) was obtained from NE followed by FFP (3.00 ton ha-1) in Jhapa and in Morang, was (4.01 ton ha-1) in NE followed by (2.05 ton ha-1) in FFP. In contrary, the higher maize yield (9.22 ton ha-1) was obtained from NE followed by FFP (4.94 ton ha-1) in Jhapa and (8.059 t ha-1)in Morang NE followed by FFP (4.52 ton ha-1). The net revenue of NE wheat in Morang was found to be increased by 344.799% while in maize the increment in net revenue of NE was only by 131.158% in Jhapa than in Morang. NE based practices produced significantly higher productivity and profitability in comparison with FFP. Int. J. Appl. Sci. Biotechnol. Vol 6(1): 45-52